IMPULSIVE BUYING IN DIGITAL COMMERCE: THE ROLE OF PERSONALITY TRAITS, WEBSITE QUALITY, AND ONLINE REVIEW CREDIBILITY - Preety; Ahlawat, Pardeep K. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the impact of personality traits, website design, and online review credibility on impulsive buying behavior in e-commerce. Using a quantitative approach, data from 500 online consumers were analyzed through Structural Equation Modeling (SEM) to uncover key psychological and technological drivers of impulsivity. The findings reveal that personality traits, particularly impulsiveness and the need for stimulation, significantly influence spontaneous purchasing behavior. Additionally, website quality encompassing usability, aesthetics, and ease of navigation enhances consumer engagement, increasing the likelihood of impulsive decisions. Online review credibility also plays a crucial role, as consumers are more inclined to make unplanned purchases when they perceive peer-generated reviews as authentic and informative. The study highlights the intricate interplay between psychological predispositions and external digital stimuli in shaping impulse buying tendencies. These insights provide theoretical contributions by extending consumer behavior models and offer practical implications for e-commerce businesses aiming to optimize website design, enhance review credibility, and implement personalized marketing strategies. While facilitating consumer engagement, ethical considerations must be maintained to prevent manipulative marketing practices. Future research should explore cultural variations, longitudinal trends, and the influence of emerging technologies on digital consumer impulsivity to further enrich understanding in this domain.